A Scoping Review on Building Energy Mode - Ahmed Audu, Umar; Jarmai Baba Girei, Zulai; Joanna Kagai, Kaliat; Falude, Emmanuel (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Energy performance in buildings may now be defined during the design phase thanks to recent advancements in dynamic energy modeling technologies. However, due to variations in weather data processing, non-identical inputs, calculation mistakes, implementation issues, and algorithms, there are variations throughout building energy simulation (BES) systems. Building energy modeling in many contexts during a building's life cycle are all covered in the literature this study reviewed. The goals of building performance simulation in practice, solutions achieved through building performance simulation, and the building industry were all explored in this research. One of the main topics is building performance simulation that needs to be addressed in the future. Four characteristics may be used to describe the problems and prospects of building performance simulation: obtaining high-quality data via innovative software or hardware technologies, quick and efficient modeling and optimization methods, and intelligence enhancement in large-scale modeling techniques like urban simulation and building design and operation workflows. The barriers outlined above will give rise to different kinds of theoretical or engineering problems in different building energy modelling application scenarios. The goal of engineers in business and researchers in academia is to find or enhance answers to these problems.